Functioning of Internal Control System of the Supply Chain System in Commercial Bank - V. Rykov, Sergey (International Journal of Supply Chain Management, 2020)
The supply chain has major impact on the company's business strategy directly affecting its operational costs. The article presents the organizational basis for the internal control functioning of the commercial bank supply chain policy. The subject of this paper is the analysis of various fields of internal audit of the supply chain as well as evaluating the characteristics of individual elements of the chain with consideration to appropriateness and integration of those elements. They determined internal control tools, information base, and the elements of the internal control system of commercial credit organizations.